Dropouts From Sublingual Immunotherapy and the Transition to Subcutaneous Immunotherapy in House Dust Mite-Sensitized Allergic Rhinitis Patients - Chen, Huan; Gong, Guo-qing; Ding, Mei; Dong, Xiang; Sun, Yuan-li; Wan, Lang; Gao, Ya-dong (Frontiers in Allergy, 2022)
Purpose: Both subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT) are effective in reducing symptoms and medication scores and inducing long-term efficacy in patients with allergic rhinitis (AR). However, SLIT has been associated with poor patient adherence. This study investigates the factors impacting dropout rates from SLIT in house dust mite (HDM)-sensitized AR patients. Methods: A retrospective study was performed to analyze dropout rates and reasons in AR patients receiving Dermatophagoides farinae (Der f) SLIT with a follow-up period of 2 years. Results: A total of 719 HDM-sensitized AR patients received Der f-SLIT. Dropout rates increased with time and most occurred after 1 year of SLIT. By month 24, 654 (91%) patients had discontinued SLIT. The dropout rates by month 24 were 100, 90.1, and 91.1% in children <5 years old, children aged 5–18 years old, and adults ≥ 18 years old, respectively. Combination with allergic asthma and mono- or multi-sensitization to other aeroallergens did not affect the dropout rates. The most common self-reported reasons for dropouts were refusal of continuation, dissatisfaction with the efficacy, transition to SCIT, and adverse effects. Refusal of continuation increased with age, whereas transition to SCIT decreased with age. Ninety-seven cases transitioned from SLIT to SCIT, and the transition rates increased with time. Comorbid allergic asthma did not affect the transition rates. However, multi-sensitization was associated with a slightly higher rate of transition to SCIT. The most common reason for the transition was dissatisfaction with the efficacy (54.6%), which was only reported by patients older than 5 years. For children who began SLIT at younger than 5 years old, the most common reason (81.2%) for transition was age reaching 5 years. Conclusions: HDM-SLIT has a very high dropout rate, which is mainly due to refusal of continuation and dissatisfaction with the efficacy. Transitioning from SLIT to SCIT may help keep these patients on AIT and thus increase adherence and long-term efficacy.